2018
DOI: 10.1002/1873-3468.13248
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quaternary structure cause a kinetic asymmetry of glutamate racemase‐catalyzed homocysteic acid racemization

Abstract: Glutamate racemases (GR) catalyze the racemization of d- and l-glutamate and are targets for the development of antibiotics. We demonstrate that GR from the periodontal pathogen Fusobacterium nucleatum (FnGR) catalyzes the racemization of d-homocysteic acid (d-HCA), while l-HCA is a poor substrate. This enantioselectivity arises because l-HCA perturbs FnGR's monomer-dimer equilibrium toward inactive monomer. The inhibitory effect of l-HCA may be overcome by increasing the total FnGR concentration or by adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the increase in glutamate in this study also indicated more biomaterials available for the synthesis of peptidoglycan in the cell wall of gentamicin-resistant E. coli [ 30 ]. The glutamate racemases catalyzing the synthesis of D-glutamate from its L-isomer could be used as targets for antibiotic treatment and the development of antibiotics [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increase in glutamate in this study also indicated more biomaterials available for the synthesis of peptidoglycan in the cell wall of gentamicin-resistant E. coli [ 30 ]. The glutamate racemases catalyzing the synthesis of D-glutamate from its L-isomer could be used as targets for antibiotic treatment and the development of antibiotics [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical examples include Fusobacterium nucleatum and B. subtilis glutamate racemase, which have K m values of 1.04 and 1.07 mM and 14 and 1.24 mM, respectively. 166 In contrast, O -ureidoserine racemase which has reported K m values 46 of 12 and 32 mM for S - and R-O -ureidoserine, respectively. In contrast, the K m for S , S -diaminopimelate (2,6-diaminoheptanedioic acid) for M. tuberculosis diaminopimelate epimerase is only 166 μM, 167 significantly lower than the K m values for other amino-acid racemases/epimerases.…”
Section: Catalytic Efficiency Of Racemases and Epimerasesmentioning
confidence: 99%
“…Similarly, k cat /K m is reported to be 16 730 and 15 294 M À1 s À1 for F. nucleatum glutamate racemase for S-and R-Glu, while the corresponding values are 3000 and 3806 M À1 s À1 for the B. subtilis enzyme. 166 In contrast, M. tuberculosis diaminopimelate epimerase 167 k cat /K m values for other racemases and epimerases tend to be higher and this is often related to the lower K m values observed for these larger substrates. For example, mandelate racemase (6.2 and 6.5 Â 10 5 M À1 s À1 for S-and R-mandelate 91 ) and the M. tuberculosis homologue of AMACR (5.23 Â 10 6 and 6.0 Â 10 6 M À1 s À1 for S-and R-ibuprofenoyl-CoA, 146 respectively).…”
Section: Catalytic Efficiency Of Racemases and Epimerasesmentioning
confidence: 99%
See 1 more Smart Citation